Effect of grape seed proanthocyanidin on the structural and physicochemical properties of bread during bread fermentation stage - Tong Jiang; Hong Wang; Peihua Xu; Yifan Yao; Yilong Ma; Zhaojun Wei; Xiangli Niu; Yafang Shang; Dong Zhao (Current Research in Food Science, 2023)
Bread was prepared using wheat flour with grape seed proanthocyanidin (GSP) (0.4%). GSP improved the textural properties of bread including hardness, cohesiviness, gumminess and chewiness. At the last stage of fermentation, GSP reinforced the gluten microstructure with increased the disulfide bonds and hydrophobic interaction and α-helix in the secondary structures. Moreover, GSP addition could increase the total phenolics and antioxidative acitivity of the bread significantly. In addition, the degree of fermentation had a strong influence on the dough forces, and the reasonable control of bread fermentation time was beneficial to improve the bread quality, which provided a reference for the bread processing industry.